Inward FDI performance in the muslim world: assesing business and political environments - Md., Moniruzzaman (SESRIC, Turkey, 2010)
This article aims to make a survey of business and political environments for inward Foreign Direct Investment performance of the Muslim countries. It offers a cross-country analysis of the 57 Muslim majority countries’ FDI performance during 1995-2007. The research finds that the business environment in the Muslim countries is not favourable for smooth transactions, and secondly, there exists a high level of political instability throughout the Muslim world. Unfavourable business environment and a high level of political instability might be held responsible for low FDI performance in the Muslim countries.